2022
DOI: 10.1016/j.celrep.2022.110393
|View full text |Cite
|
Sign up to set email alerts
|

B cell receptor repertoire kinetics after SARS-CoV-2 infection and vaccination

Abstract: B cells are important in immunity to both SARS-CoV-2 infection and vaccination, but B cell receptor (BCR) repertoire development in these contexts has not been compared. We analyse serial samples from 171 SARS-CoV-2-infected individuals and 63 vaccine recipients, and find the global BCR repertoire differs between them. Following infection, IgG1/3 and IgA1 BCRs increase, somatic hypermutation (SHM) decreases and, in severe disease, IgM and IgA clones are expanded. In contrast, after vaccination the proportion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 93 publications
5
47
0
Order By: Relevance
“…In addition to this, T cell memory also plays an important role in protection. The way in which these aspects of memory are impacted by different vaccine schedules, and by infection itself 37 , in different ethnic groups, will be important in optimising vaccine strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, T cell memory also plays an important role in protection. The way in which these aspects of memory are impacted by different vaccine schedules, and by infection itself 37 , in different ethnic groups, will be important in optimising vaccine strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Mature B cells can react strongly to foreign antigens, resulting in B cell stimulation, clonal expansion, and ultimately, the secretion of high-affinity antibodies in the blood [ 3 ]. During B cell development, single variable (V), diversity (D), and joining (J) genes are selected from multiple distinct copies and imprecisely joined to create a B cell receptor (BCR) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Global features of the BCR repertoire have been studied by high-throughput bulk RNA sequencing of immunoglobulin heavy chain (IgH) genes [ 5–7 ]. IgH BCR repertoires studies showed different usage of V gene and immunoglobulin isotype switch post several types of COVID-19 vaccination or virus infection in subjects [ 8 ]. The usage of IGHV1-24 was increased in the severely infected group during the early stage, while no similar trend was observed post-BNT162B2 SARS-CoV-2 vaccination [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations